2010
DOI: 10.1590/s0004-282x2010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Brain SPECT in mesial temporal lobe epilepsy: comparison between visual analysis and SPM

Abstract: Objective: To compare the accuracy of SPM and visual analysis of brain SPECT in patients with mesial temporal lobe epilepsy (MTLE). Method: Interictal and ictal SPECTs of 22 patients with MTLE were performed. Visual analysis were performed in interictal (VISUAL(inter)) and ictal (VISUAL(ictal/inter)) studies. SPM analysis consisted of comparing interictal (SPM(inter)) and ictal SPECTs (SPM(ictal)) of each patient to control group and by comparing perfusion of temporal lobes in ictal and interictal studies amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…For TLE lateralization, SPECT and PET are currently the principle imaging modalities used, and not DSC perfusion MRI. Amorim et al (21) found that the sensitivity of SPECT used for ictal TLE surpassed that of interictal TLE, where the sensitivity was low (32.3 -55.3%). In the present study, the results using DSC perfusion MRI showed that the AIs from nine TLE interictal patients were significantly higher than those of the healthy volunteers, and the ipsilateral side could be determined accurately.…”
Section: Advantages and Disadvantages Of Dsc-mri Application In Tlementioning
confidence: 99%
“…For TLE lateralization, SPECT and PET are currently the principle imaging modalities used, and not DSC perfusion MRI. Amorim et al (21) found that the sensitivity of SPECT used for ictal TLE surpassed that of interictal TLE, where the sensitivity was low (32.3 -55.3%). In the present study, the results using DSC perfusion MRI showed that the AIs from nine TLE interictal patients were significantly higher than those of the healthy volunteers, and the ipsilateral side could be determined accurately.…”
Section: Advantages and Disadvantages Of Dsc-mri Application In Tlementioning
confidence: 99%
“…SPECT is a well-established imaging modality for patients with epilepsy, 2,4 cerebrovascular disease, 2,5 neoplastic processes, 2,6 and dementia. 2,79 A few studies have also examined its use in head trauma 10–13 and traumatic anosmia.…”
Section: Introductionmentioning
confidence: 99%
“…SPM is an automatic statistical analysis tool for neuroimaging. It has been used in brain SPECT in some pathologies and our group has already applied this tool in epilepsy 7,8 . The purpose of this study was to demonstrate brain perfusion changes due to neuronal activation after functional electrical stimulation in patients with brain stroke and traumatic lesions.…”
mentioning
confidence: 99%